Do Workers Prefer Increasing Wage Profiles? - Loewenstein, George; Sicherman, Nachum (Journal of Labor Economics, 1991)
The authors present survey data challenging the assumption implicit in analyses of labor supply that, all else being equal, workers prefer declining over increasing wage profiles. The authors test several explanations for their results, including that (1) there is something special about wages (e.g., their association with productivity), as opposed to other types of payments, that induces the preference for increasing wages; (2) utility depends not only on absolute levels of consumption, but also on changes in consumption over time; and (3) respondents who prefer increasing wage profiles are irrational and would change their behavior if the rationale for preferring declining wages were explained. Copyright 1991 by University of Chicago Press.